(3cJGH HQSjS aj JOHjQ GdQLd defRdgs - (3GdMcje HQSjS HQhfSs
(3ChdgG (B:s
(3bGd Cf CeQ GdefRd jJe HCQHY NUGd ChdgG GdeGd hGdKGfi ai GdNOe hGdKGdK GdeQCI hGdQGHY GdhdO s
(3BNQgG (B:s
(3aGf GdjSjQ ef GdNWC ai ChGjd GdCTjGA hCUhdgG djS HjSjQ GdVQQ hcPdc GdefaYI ai jSjQ GdUhGH dGf GdCTjGA JHfi Ydi Jdc GdCUhd s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JjehQ (B290) s
Keywords: (3GdSjGSI hGdGLJeGYs